The Influence of Command Teaching Style on Learning Outcomes of Futsal Game Skills - Yanyan Sofyan; Yudha M Saputra; Herman Subarjah (STKIP Muhammadiyah Kuningan, 2022)
This study aims to determine the effect of the Teaching style command on learning outcomes of shooting in the soccer game of class IV-C students of SDN 159 Sekejati Bandung. The method used is an experimental method with the type of one-group pretest-posttest design. The number of samples is 20 students from classes IV-C. The data collection uses the technique futsal skill game. The result of this study indicates that there is an effect of the command style on the learning outcomes of the command teaching style on the inner foot passage learning in futsal games at class IV-C students of SDN 159 Sekejati Bandung because the t-count is more significant than t-table (16,580 > 2,093).